Productivity pattern of universities in Kerala: A scientometric analysis - Aswathy S and A Gopikuttan (Annals of Library and Information Studies, 2013)
The study analyses the publication pattern of faculty members of three universities in Kerala viz., University of Kerala, Mahatma Gandhi University and University of Calicut. Authorship pattern, Degree of Collaboration, the appropriateness of Lotka’s Inverse Square Law and year-wise and designation-wise distributions have been studied. The year-wise distribution of publications indicates that there is a growth in the number of publications. It is found that multi-authorship dominates among university teachers and there is no statistically significant difference between the experience and productivity. Designation-wise Degree of Collaboration shows that Professors are having a high Degree of Collaboration which indicates that increase in the age and experience results in more collaborative papers. The Lotka’s inverse square law seems to be rejected for the present data set.